Kajian pembangunan kerangka model usahawan wanita - Md Isa, Filzah; Cheng, Wei Hin; Hashim, Norashidah; Abdullah, Haim Hilman; Mohd Yunus, Jasmani; Hoe, Chee Hee (Universiti Utara Malaysia, 2011)
This study aims to examine and gather detailed information on the business achievement of several women entrepreneurs in Malaysia and to record the profiles of the women entrepreneurs who involved in the study.In addition, this study also identifies issues, problems and challenges faced by the women entrepreneurs and to determine the critical success factors (critical success factors-CSF), decision making styles, leadership styles, entrepreneurial skills, spiritual factors and socialization factors that influence their business success.Based on the findings, the study has developed a model that could be used as a basis for more studies that may assist in the continuous learning process of students and entrepreneurs (both new and existing ones) in Malaysia.Several recommendations regarding training programs for these groups are also provided. Data collection methods used in the study include the primary data, secondary data sources, and also observations that help to ensure the findings of the study are able to comprehensively answer all the research questions.A total of 11 successful women entrepreneurs (comprised of Malay, Chinese and Indian) in Malaysia involved in this study. In general, the research findings indicate that the main determinant factors of the women entrepreneurs’ business success are individual, organizational and environmental factors.Furthermore, support and assistance from the government agencies, entrepreneurs’ moral and spiritual values, and networking and ‘guanxi’ factors could act as the moderator to the respondents’ business success.